2013
DOI: 10.1001/jamadermatol.2013.4646
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antimycobacterial Therapy in Chronic Cutaneous Sarcoidosis

Abstract: IMPORTANCE Sarcoidosis is a chronic granulomatous disease for which there are limited therapeutic options. This is the first randomized, placebo-controlled study to demonstrate that antimycobacterial therapy reduces lesion diameter and disease severity among patients with chronic cutaneous sarcoidosis. OBJECTIVE To evaluate the safety and efficacy of once-daily antimycobacterial therapy on the resolution of chronic cutaneous sarcoidosis lesions. DESIGN AND PARTICIPANTS A randomized, placebo-controlled, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 34 publications
1
52
0
1
Order By: Relevance
“…Working under the hypothesis that sarcoidosis is caused by an active replicating mycobacterial infection, Drake and colleagues studied a series of patients with severe cutaneous and pulmonary sarcoidosis who were treated with a four-drug regimen of concomitant levofloxacin, ethambutol, azithromycin, and rifampin (CLEAR) [135]. Drug dosages were based on guidelines for the treatment of atypical mycobacterial infection.…”
Section: Controversy In Mycobacterial Pathogenesis Of Sarcoidosismentioning
confidence: 99%
“…Working under the hypothesis that sarcoidosis is caused by an active replicating mycobacterial infection, Drake and colleagues studied a series of patients with severe cutaneous and pulmonary sarcoidosis who were treated with a four-drug regimen of concomitant levofloxacin, ethambutol, azithromycin, and rifampin (CLEAR) [135]. Drug dosages were based on guidelines for the treatment of atypical mycobacterial infection.…”
Section: Controversy In Mycobacterial Pathogenesis Of Sarcoidosismentioning
confidence: 99%
“…A recent randomized single-blind controlled trial in 29 subjects evaluated the use of antimycobacterial therapy (concomitant levofloxacin, ethambutol, azithromycin, and rifampin-clear) versus placebo in patients with cutaneous sarcoidosis [34]. Intention-to-treat analysis showed a significant reduction in lesion size in the treatment group compared to placebo.…”
Section: Antimycobacterial Therapymentioning
confidence: 99%
“…Intention-to-treat analysis showed a significant reduction in lesion size in the treatment group compared to placebo. An open-label trial in pulmonary sarcoidosis likewise suggested that CLEAR therapy over eight weeks may lead to improved quality of life, vital capacity, and 6-min walk distance [35]. Currently, a phase II clinical trial is evaluating the efficacy of CLEAR in patients with progressive pulmonary sarcoidosis (NCT02024555).…”
Section: Antimycobacterial Therapymentioning
confidence: 99%
“…Concomitant levofloxacin, ethambutol, azithromycin, and rifampin (CLEAR) is a synergistic antibiotic regimen recently utilized as a clinical trial therapy for chronic pulmonary sarcoidosis exhibiting decreased levels of LCK and NF-κB [134,135]. Clonal exhaustion, or anergy, of T-cells is characterized by a decrease in NF-κB, CD3 delta and LCK [136].…”
Section: Antimicrobialmentioning
confidence: 99%
“…In the event of LCK inactivation, no phosphorylation of CD3 tyrosine residues on activation motifs occurs which blocks CD4 T-cell response [136]. Restoration of LCK and NF-κB expression by antimycobacterial therapy in chronic sarcoidosis patients improves forced vital capacity while also further indicting Mycobacterium as a putative contributor and CLEAR as a therapeutic alternative [134].…”
Section: Antimicrobialmentioning
confidence: 99%